(untitled) (Theatrum historiae, 2009)
In this essay the author tries to conclude one aspect of his Ph.D. dissertation which is in historical way analysing and interpreting different types of memoirs and interviews of Czechoslovak soldiers from WW II. Inspired by concepts of Maurice Halbwachs (cadres de memoire) and Pierre Nora (lieux de memoire) and also basing on oral history metodology, he is consequently (re)constructing contours of ex-soldiers war and postwar memory. In this case he tries to describe symbolic „image“ of war allies and war enemies as place of memory and everyday life. Finaly as result it could be stated that these symbolic images take very important part among another ones (e.g. influence of so-called „Munich Myth“, reception of „great“ political events, perception of „home and homeland“, or attitudes toward Czechoslovak army grounds and political elites) and they play a key role in the process of (re)creation of individual and collective memory and identity of ex-Czechoslovak combattants.